2021
DOI: 10.1371/journal.pone.0253647
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of potentially unrelated AmpC beta-lactamase producing Enterobacteriaceae from cattle, cattle products and hospital environments commonly harboring the blaACC resistance determinant

Abstract: The occurrence and genetic relatedness of AmpC beta-lactamase producing Enterobacteriaceae isolated from clinical environments, groundwater, beef, human and cattle faeces were investigated. One hundred seventy-seven (177) samples were collected and cultured on MacConkey agar. A total of 203 non-repetitive isolates were characterised using genus/species-specific PCRs and the identified isolates were subjected to antibiotic susceptibility testing. The production of AmpC beta-lactamases was evaluated using cefoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…AmpC was detected in 49/321(15.2%) isolates. Matloko et al 22 reported confirmation of AmpC in 50% of isolates while Hashemi et al 23 reported 28% positivity. It detects inducible, derepressed and constitutive AmpC in both chromosomal and plasmid AmpC producers.…”
Section: Discussionmentioning
confidence: 99%
“…AmpC was detected in 49/321(15.2%) isolates. Matloko et al 22 reported confirmation of AmpC in 50% of isolates while Hashemi et al 23 reported 28% positivity. It detects inducible, derepressed and constitutive AmpC in both chromosomal and plasmid AmpC producers.…”
Section: Discussionmentioning
confidence: 99%
“…The AmpC-associated genes that have been identified in this study, namely bla CMY , bla MOX , bla FOX , bla EBC , and bla DHA , have been previously documented in both humans and animals in certain countries, including India [57,[70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…Further, bla DHA-1 was detected in Enterobacterales, such as Proteus mirabilis , E. coli and K. pneuomoniae , collected from pig production in India and Korea [ 12 , 27 ]. Food of animal origin can also be considered a source of bla DHA-1 as it has been described in a number of publications in recent years, especially in Pseudomonas aeruginosa collected from bovine and ovine meat, raw milk and fishery products from Iran [ 28 , 29 , 30 , 31 ] but also in K. pneumoniae and E. coli strains isolated from shrimp in Germany, in E. coli isolated from beef products in South Africa and in K. pneumoniae isolated from ready-to-eat sandwiches in Algeria [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%